2022
DOI: 10.3389/fpsyg.2022.906190
|View full text |Cite
|
Sign up to set email alerts
|

The sweet spot between predictability and surprise: musical groove in brain, body, and social interactions

Abstract: Groove—defined as the pleasurable urge to move to a rhythm—depends on a fine-tuned interplay between predictability arising from repetitive rhythmic patterns, and surprise arising from rhythmic deviations, for example in the form of syncopation. The perfect balance between predictability and surprise is commonly found in rhythmic patterns with a moderate level of rhythmic complexity and represents the sweet spot of the groove experience. In contrast, rhythms with low or high complexity are usually associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 97 publications
(118 reference statements)
5
23
0
Order By: Relevance
“…Our results support a crucial role of cortico-striatal circuits and dopamine in the pleasurable urge to move to music 8,93 . Both PD groups showed a flattening of the U-shaped relation between rhythmic complexity and ratings of pleasure and wanting to move compared to healthy age-matched controls.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results support a crucial role of cortico-striatal circuits and dopamine in the pleasurable urge to move to music 8,93 . Both PD groups showed a flattening of the U-shaped relation between rhythmic complexity and ratings of pleasure and wanting to move compared to healthy age-matched controls.…”
Section: Discussionsupporting
confidence: 77%
“…In this context, strongly weighted syncopations drive the urge to move, either directly to reinforce the metrical model, or indirectly via covert adjustments to that model. In terms of pleasure, by challenging our metric models, these syncopations potentiate model improvement 93 , which is itself intrinsically rewarding 108,109 . The weight of prediction errors due to syncopations depends on both the rhythmic context 110 and the strength of the listener’s metrical model 111 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on 970,220 comments on 155 music videos, our findings suggest that the term groove is used to describe movement-and pleasure-related subjective experiences, as well as objective musical qualities that are tightly linked to the genres funk, soul, and R&B. Resonating with previous studies, groove terms were very likely to co-occur with movement (e.g., Janata et al, 2012;Madison, 2006;Stupacher et al, 2013), timing (e.g., Keil, 1995Senn et al, 2016;Witek et al, 2014), and flow/smoothness (Duman et al, 2021;Stupacher 2019) themes. Our dataset did not allow for conclusions about the link between groove and social bonding, which has been proposed by previous studies (Dotov et al, 2021;Duman et al, 2021Duman et al, , 2022Stupacher et al, 2022). In general, the study shows that text-mining approaches to analyzing YouTube comments provide an interesting perspective on how a general population of listeners discusses music.…”
Section: Discussionmentioning
confidence: 73%
“…The connection between timing, rhythm, and groove is often-discussed. Groove has for example been related to moderate amounts of syncopation (Matthews et al, 2019;Sioros et al, 2014;Stupacher et al, 2022;Witek et al, 2014;Witek, 2017) or to microtiming (Câmara & Danielsen, 2020;Keil, 1995;Senn et al, 2016). Microtiming, understood as intended expressive timing deviations in music performances, has been argued to contribute to a sense of movement and collective participation (Keil, 1995, cf., Butterfield, 2010.…”
Section: Groove As An Objective Qualitymentioning
confidence: 99%
“…To the best of our knowledge, the psychological study of groove started approximately twenty years ago with pioneering studies by Madison (2001Madison ( , 2003 who found that the groove experience seemed to be a consistent trait of music perception in humans, and that it transcended the boundaries of musical genres and cultures (Madison, 2006;Madison et al, 2011). In the 2010s, groove research grew into a budding field of investigation; for a recent review of the psychological and neurological groove literature, see Stupacher, Matthews, et al (2022). Senn et al (2019) proposed a psychological model of musical groove that is centered on the urge to move.…”
Section: Introductionmentioning
confidence: 99%